Wild vertebrates and their representation by urban/rural students in a region of northeast Brazil - José Valberto de Oliveira; Sérgio de Faria Lopes; Raynner Rilke Duarte Barboza; Dilma Maria de Melo Brito Trovão; Maiara Bezerra Ramos; Rômulo Romeu Nóbrega Alves (BMC, 2019)
Abstract Background Recognition of the diversity of living beings, including the classification and naming of species, is a fundamental condition for biological literacy with the aim of developing critical awareness of human relationships with nature, and for which formal education plays an important role. The present study aimed to analyze the representation that urban/rural students have for wild vertebrates and their main sources of knowledge. Methods Data collection took place in three public schools, one urban and two rural, in the municipality of Campina Grande, Paraíba, Brazil. Questionnaires were given to 990 students (528 urban and 462 rural), distributed among all the grades that comprise middle school (Ensino Fundamental II, grades 6-9) and high school (Ensino Médio, grades 10-12) education. Results A total of 5877 citations were mentioned by the students, which corresponded to 224 distinct animals with 166 (72.0%) being wild vertebrates, 24 (25.7%) being domestic vertebrates, and 34 (2.3%) being invertebrates. Mammals and reptiles had the greatest observed richness of citations, while mammals (H' = 3.37), birds (H' = 2.84), and invertebrates (H' = 2.94) had the greatest diversity. Positive correlations were found between citations of wild vertebrates and family income (rt = 0.06; P < 0.05) and curricular development (rs = 0.08; P < 0.01); negative correlations were found between curricular development and citations of domestic animals (rs = − 0.22; rs = − 0.11 P < 0.01) and between age group and citations of invertebrates (r = − 0.14; rs = − 0.11 P < 0.01). As for the sources of knowledge regarding the animals indicated by the students, "media," "daily experiences," "tradition" (here understood as knowledge resulting from interactions with parents and experienced community members), and "formal education" stood out. Conclusions Comprehension of vertebrate diversity is a fundamental condition for the development of attitudes compatible with its conservation, which emphasizes the importance of biological literacy in achieving this purpose.